Vocabulary : Applied Linguistic Perspectives. - Carter, Ronald (Routledge linguistics classics., 2012)
How do we teach and learn vocabulary? How do words work in literary texts? In this book, Ronald Carter provides the necessary basis for the further study of modern English vocabulary with particular reference to linguistic descriptive frameworks and educational contexts. Vocabulary: Applied Linguistic Perspectives includes an introductory account of linguistic approaches to the analysis of the modern lexicon in English and discusses key topics such as vocabulary and language teaching, dictionaries and lexicography and the literary, stylistic study of vocabulary. This Routledge Linguistics Clas.